Snapshots of Conformational Changes Shed Light into the NtrX Receiver Domain Signal Transduction Mechanism. Issue 20 (9th October 2015) - Fernández, Ignacio; Otero, Lisandro H.; Klinke, Sebastián; Carrica, Mariela del Carmen; Goldbaum, Fernando A.
Abstract: Brucella abortus is an important pathogenic bacterium that has to overcome oxygen deficiency in order to achieve a successful infection. Previously, we proved that a two-component system formed by the histidine kinase NtrY and the response regulator NtrX is essential to achieve an adaptive response to low oxygen tension conditions. Even though the relevance of this signaling pathway has already been demonstrated in other microorganisms, its molecular activation mechanism has not yet been described in detail. In this article, we report the first crystal structures from different conformations of the NtrX receiver domain from B . abortus, and we propose a sequence of events to explain the structural rearrangements along the activation process. The analysis of the structures obtained in the presence of the phosphoryl group analog beryllofluoride led us to postulate that changes in the interface formed by the α4 helix and the β5 strand are important for the activation, producing a reorientation of the α5 helix. Also, a biochemical characterization of the NtrX receiver domain enzymatic activities was performed, describing its autophosphorylation and autodephosphorylation kinetics. Finally, the role of H85, an important residue, was addressed by site-directed mutagenesis. Overall, these results provide significant structural basis for understanding the response regulator activation in this bacterial two-component system. Graphical Abstract: Highlights: A molecular description of the activation mechanism of NtrX is not available. Different crystal structures of NtrX REC domain are reported for the first time. Phosphorylation stabilizes a conformation of the loop β4-α4 and helices α4 and α5. Biochemical characterization of the REC domain enzymatic activities was performed. A mechanism for the signal transduction to the full-length protein is proposed.